Factors influencing the compliance of workplace safety culture in the government linked company (GLC) - Isa A.A.M.; Wahab W.A.; Omar R.C.; Nordin M.Z.M.; Taha H.; Roslan R. (EDP Sciences, 2023)
This research focused on five factors; the management commitments towards safety, availability of safety rules and procedures, safety communication and feedback, the effectiveness of safety training, and the acquisition of safety knowledge that contributes to compliance of safety culture in the government-linked companies (GLC), by exploring various dimensions by which converge into achieving organizational safety performance outcomes. The importance of safety performance in the GLC is to ensure the employees have the right safety culture, a safe working environment, and comply with safety rules and procedures. The contribution of the findings of this study may provide knowledge of existing safety management practices in Malaysia's Government Linked Company (GLC) and facilitate the organizations in evaluating the importance of safety management on their performance. This study also emphasizes the relationship between the five factors mentioned towards the compliance of safety culture in the organization. Besides that, it also provides an empirical review on which components of safety management practices have a better relationship with the organizational safety culture. Based on the results obtained, there is a positive correlation between management commitments towards safety, availability of safety rules and procedures, safety communication and feedback, the effectiveness of safety training, and acquisition of safety knowledge with regards to employees' safety compliance towards a better safety culture in the organization. The Authors, published by EDP Sciences.